The psychometric properties of the Paper and Pencil Games Level 2 for Tigrigna-speaking children in Eritrea - Tecle, Hagos Ghebremicael (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2003.